2019
DOI: 10.1038/s41416-019-0477-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and metabolic rewiring of colorectal cancer cells expressing the oncogenic KRASG13D mutation

Abstract: BackgroundActivating mutations in KRAS frequently occur in colorectal cancer (CRC) patients, leading to resistance to EGFR-targeted therapies.MethodsTo better understand the cellular reprogramming which occurs in mutant KRAS cells, we have undertaken a systems-level analysis of four CRC cell lines which express either wild type (wt) KRAS or the oncogenic KRASG13D allele (mtKRAS).ResultsRNAseq revealed that genes involved in ribosome biogenesis, mRNA translation and metabolism were significantly upregulated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 55 publications
3
43
0
Order By: Relevance
“…Likewise, our results that phosphorylation changes contribute to PPIN rewiring may "repurpose" kinase inhibitors as PPIN rewiring agents. We recently showed that mtKRAS also profoundly changes the metabolic and transcriptional landscapes of CRC cells 53 confirming that mtKRAS widely affects cellular regulation on different levels. Surprisingly, our analysis shows that a low-level expression of mtKRAS is compatible with normal (i.e., untransformed) biochemical and biological behavior.…”
Section: Discussionmentioning
confidence: 77%
“…Likewise, our results that phosphorylation changes contribute to PPIN rewiring may "repurpose" kinase inhibitors as PPIN rewiring agents. We recently showed that mtKRAS also profoundly changes the metabolic and transcriptional landscapes of CRC cells 53 confirming that mtKRAS widely affects cellular regulation on different levels. Surprisingly, our analysis shows that a low-level expression of mtKRAS is compatible with normal (i.e., untransformed) biochemical and biological behavior.…”
Section: Discussionmentioning
confidence: 77%
“…Although it is well documented that ribosome biogenesis can be controlled by growth factor receptors through MAPK/RAS/signaling [52,91] and that constitutive activation of KRAS represents a major determinant of some CRC subtypes, only few studies have explored the contribution of the oncogenic RAS pathway in ribosome biogenesis-mediated colorectal tumorigenesis. Human colorectal cancer cell lines with constitutive KRAS activation display a gene signature enriched in ribosome biogenesis and translation factors [92]. A recent report showed that the cysteine protease calpain-2 is involved in the inhibition of 47S pre-rRNA biogenesis as well as in the disruption of nucleolar integrity in human CRC DLD-1 cells [93].…”
Section: Myc and Ras Regulations Of Ribosome Biogenesis In Crcmentioning
confidence: 99%
“…The second-most common mutation in CRC is found in KRAS, leading to constitutively active MAPK signaling, which is also implicated in the regulation of rDNA synthesis [67]. Additionally, CRC cells with mutant KRAS show increased expression of genes involved in ribosome biogenesis and mRNA translation; this is associated with enhanced protein synthesis in CRC cells as compared to cells with wild-type KRAS [68]. Finally, the mTOR signaling pathway is a master regulator of ribosome biogenesis and is highly deregulated in CRC [69].…”
Section: Deregulation Of Ribosome Biogenesis In Crcmentioning
confidence: 99%